Systematic Identification, Fragmentation Pattern, And Metabolic Pathways of Hyperoside in Rat Plasma, Urine, And Feces by UPLC-Q-Exactive Orbitrap MS - Li Ji; Wenjun Shi; Yanling Li; Jing He; Guang Xu; Ming Qin; Yuying Guo; Qun Ma (Journal of Analytical Methods in Chemistry)
Hyperoside is a natural flavonol glycoside, which has antioxidation, antitumor, and anticancer activities together with other healthy effects like improving cardiovascular function, protecting the liver, and regulating the immune system. It is a popular compound used in the traditional Chinese medicine and different studies on hyperoside are present in the literature. However, studies on the metabolism of hyperoside in vivo were not comprehensive. In this study, UPLC-Q-Exactive Orbitrap MS technology was used to establish a rapid and comprehensive analysis strategy to explore the metabolites and metabolic process of hyperoside in rats. The metabolites of hyperoside were systematically identified in rat plasma, urine, and feces. According to the hyperoside standard substance and relevant works of literature, a total of 33 metabolites were identified, including 16 in plasma, 31 in urine, and 14 in feces. Among them, the metabolites quercetin and dihydroquercetin were unambiguously confirmed by comparison with standard substances. In addition, 13 metabolites had not been reported in hyperoside metabolism-related articles at present. The metabolic reactions of hyperoside in vivo were further explored, including phase I metabolism (hydroxylation, dehydroxylation, glycoside hydrolysis, hydrogenation, and hydration) and phase II metabolism (methylation, acetylation, sulfation, and glucuronide conjugation). The fragment ions of hyperoside and its metabolites were usually produced by glucoside bond hydrolysis, the neutral loss of (CO + OH), COH, CO, O, and Retro-Diels Alder (RDA) cleavage. In conclusion, this study comprehensively characterized the metabolism of hyperoside in rats, providing a basis for exploring its various biological activities.